Bursting thalamic responses in awake monkey contribute to visual detection and are modulated by corticofugal feedback - Ortuño, Tania; Grieve, Kenneth L.; Cao, Ricardo; Cudeiro, Javier; Rivadulla, Casto (Frontiers in Behavioral Neuroscience, 2014)
The lateral geniculate nucleus is the gateway for visual information en route to the visual cortex. Neural activity is characterized by the existence of 2 firing modes: burst and tonic. Originally associated with sleep, bursts have now been postulated to be a part of the normal visual response, structured to increase the probability of cortical activation, able to act as a “wake-up” call to the cortex. We investigated a potential role for burst in the detection of novel stimuli by recording neuronal activity in the LGN of behaving monkeys during a visual detection task. Our results show that bursts are often the neuron’s first response, and are more numerous in the response to attended target stimuli than to unattended distractor stimuli. Bursts are indicators of the task novelty, as repetition decreased bursting. Because the primary visual cortex is the major modulatory input to the LGN, we compared the results obtained in control conditions with those observed when cortical activity was reduced by TMS. This cortical deactivation reduced visual response related bursting by 90%. These results highlight a novel role for the thalamus, able to code higher order image attributes as important as novelty early in the thalamo-cortical conversation.